1999
DOI: 10.1001/archinte.159.14.1613
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Knowledge of and Adherence to Self-care Among Patients With Heart Failure

Abstract: We observed a gap between patients receiving and absorbing or retaining information on self-care for congestive heart failure supplied by health care providers. Self-care education needs to be directed to outpatients in addition to inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
268
5
15

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(317 citation statements)
references
References 12 publications
26
268
5
15
Order By: Relevance
“…With regard to gender differences, our study indicates that women are more likely to improve their self-care behaviour compared to men. This confirms by Ni et al [26] who found a difference in favour of women, whereas Artinian et al [35] found no gender differences. Although the present study is small and one should be careful to draw general conclusions, our results indicate that education about self-care behaviour maybe should be different for men and women.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…With regard to gender differences, our study indicates that women are more likely to improve their self-care behaviour compared to men. This confirms by Ni et al [26] who found a difference in favour of women, whereas Artinian et al [35] found no gender differences. Although the present study is small and one should be careful to draw general conclusions, our results indicate that education about self-care behaviour maybe should be different for men and women.…”
Section: Discussionsupporting
confidence: 82%
“…There were no significant gender differences regarding quality of life. Self-care behaviour did not change significantly from baseline (31, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]) to 12 month (29 [22,). There were no gender differences in self-care behaviour measured by the EHFScBS between baseline and 12 months.…”
Section: Study Patientsmentioning
confidence: 99%
“…Important physician factors that may contribute to CHF exacerbations are under-utilization of established therapy such as ACE inhibitors that can reduce morbidity and mortality, and suboptimal education, including low rates of general and dietary counseling (Smith et al, 1998;CONSENSUS, 1987;SOLVD, 1991;IPRO, 1996). Medication and dietary nonadherence (with sodium restriction), inadequate discharge planning and follow-up, lack of social support and not seeking medical attention promptly when symptoms recur also increase the risk of CHF exacerbations (Ni et al, 1999;Ghali, Kadakia, Cooper, & Ferlinz, 1988;Chin & Goldman, 1997;Vinson, Rich, Sperry, Atul, & McNamara, 1990, Tsuyuki et al, 2001Michalsen, Konig, & Thimme, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, compliance with weighing remained high during follow-up in the intervention groups, while compliance decreased in the care as usual group. Although knowledge alone does not ensure compliance 16 , it has nevertheless been confirmed as an important determinant of compliance in the HF literature. [17][18][19][20] An explanation for low compliance with weighing could be that many HF patients do not recognize the importance of daily weighing to check for fluid retention.…”
mentioning
confidence: 99%
“…[17][18][19][20] An explanation for low compliance with weighing could be that many HF patients do not recognize the importance of daily weighing to check for fluid retention. 16 Also, having a stable weight over a longer period of time is another reason why patients weigh themselves less often. 21 Our study showed that providing adequate education on the importance of daily weighing is effective on increasing and maintaining compliance.…”
mentioning
confidence: 99%